2008
DOI: 10.1016/j.biocel.2008.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Decreased ER-associated degradation of α-TCR induced by Grp78 depletion with the SubAB cytotoxin

Abstract: HeLa cells stably expressing the α chain of T-cell receptor (αTCR), a model substrate of ERAD (ERassociated degradation), were used to analyze the effects of BiP/Grp78 depletion by the SubAB cytotoxin. SubAB induced XBP1 splicing, followed by JNK phosphorylation, eIF2α phosphorylation, upregulation of ATF3/4 and partial ATF6 cleavage. Other markers of ER stress, including elements of ER-associated degradation (ERAD) pathway, as well as markers of cytoplasmic stress, were not induced. SubAB treatment decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 61 publications
4
25
0
Order By: Relevance
“…2B, insets). The periphery of these structures contained both mutant PLPmh and calnexin, resembling the distended ER that has been observed under conditions of chronic ER stress (Alvarez et al, 1999;Dalal et al, 2004;Lass et al, 2008;Lin et al, 1999). The milddisease-associated mutants W162L and G245A were also present A twodimensional model of PLP topology illustrating the four TM domains, cytosolic N-and C-termini, palmitoylation sites (squiggles), and disulphide bonds (straight lines).…”
Section: Retention Of Disease-associated Plp Mutants By the Er Qualitmentioning
confidence: 80%
“…2B, insets). The periphery of these structures contained both mutant PLPmh and calnexin, resembling the distended ER that has been observed under conditions of chronic ER stress (Alvarez et al, 1999;Dalal et al, 2004;Lass et al, 2008;Lin et al, 1999). The milddisease-associated mutants W162L and G245A were also present A twodimensional model of PLP topology illustrating the four TM domains, cytosolic N-and C-termini, palmitoylation sites (squiggles), and disulphide bonds (straight lines).…”
Section: Retention Of Disease-associated Plp Mutants By the Er Qualitmentioning
confidence: 80%
“…However, treatment with SubAB results in rapid degradation of nearly all cellular BiP in a wide variety of cell lines, effectively mimicking a knock-out phenotype. The toxin has already been used to examine the role of BiP and/or ER stress in ER-associated degradation in HeLa cells 48, and regulation of gap junction function in mesangial cells 49. SubAB has also been employed to demonstrate the critical role of BiP in assembly and egress of cytomegalovirus from infected cells 50 and in production and processing of dengue virus proteins 51.…”
Section: Ab5 Toxins As Innovative Cellular Toolsmentioning
confidence: 99%
“…Recently, Xu et al reported that proteasomal degradation of Mcl-1 is required for action of p97/VCP, which mediates disparate cellular functions, including ERAD, via the ubiquitin-proteasome system (51). In HeLa cells, SubAB treatment induced activation of ERAD (20). To address whether ERAD is associated with SubAB-induced apoptosis, we carried out p97/VCP knockdown by siRNA and then determined the effect of SubAB on caspase activation.…”
Section: Subab-induced Caspase Activation Is Mediated By Perkmentioning
confidence: 99%